2015
DOI: 10.2185/jrm.2890
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of community members regarding community health workers’ activities as a measure of the impact of a training program in Amazonas, Brazil

Abstract: Objectives: The aim of this study was to evaluate the impact of community health worker (CHW) training on recognition and satisfaction regarding the performance of CHWs among members of the community in Amazonas, Brazil, which is a resource-poor area underserved with regard to medical health-care accessibility.Methods: Baseline and endline surveys concerning recognition and satisfaction with respect to CHW performance among members of the community were conducted by interview using a questionnaire before and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 18 publications
(20 reference statements)
1
19
0
1
Order By: Relevance
“…Con rming sick persons in the community was positively associated with community satisfaction. This is similar to a study conducted in Brazil which revealed that community satisfaction was positively associated with con rming sick persons in the community [29]. Therefore, con rming sick persons should be incorporated among CHW programs to improve community satisfaction.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Con rming sick persons in the community was positively associated with community satisfaction. This is similar to a study conducted in Brazil which revealed that community satisfaction was positively associated with con rming sick persons in the community [29]. Therefore, con rming sick persons should be incorporated among CHW programs to improve community satisfaction.…”
Section: Discussionsupporting
confidence: 88%
“…Monthly home visits were positively associated with community satisfaction. A study conducted in Amazonas, Brazil showed an increased community satisfaction with home visits (OR 26.66) [29]. Home visits enable community members come into contact with their community health workers and have been associated with improvement in maternal and child health [4,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Zeitz et al 65 reported on a 1-day refresher training course for CHWs that specifically focused on acute respiratory illness in children and used pretesting and post-testing of knowledge as the outcome measure of the training. This is in contrast with Kawasaki et al 48 , who carried out a 2-year study where CHWs received monthly refresher trainings, and the outcome measures were focused on behaviour change at the community level, for example, improved handwashing techniques and the number of household visits carried out by CHWs. This variation, both in terms of duration, structure and content focus, makes direct comparison between studies difficult (see online supplementary table 3 ).…”
Section: Resultsmentioning
confidence: 94%
“…Pelatihan sukarelawan kesehatan dapat meningkatkan pengetahuan dan keterampilan terkait promosi kesehatan serta meningkatkan motivasi dan kepercayaan diri (Tumbelaka et al, 2018). Selain itu, pelatihan kader juga meningkatkan kemampuan komunikasi bagi kader dan meningkatkan kepuasan terhadap peran sebagai kader (Nasir et al, 2013;Kawasaki et al, 2015). Keberlanjutan pelatihan kader kesehatan mampu meningkatkan peran kader dalam melakukan tugasnya (Kok et al, 2015).…”
Section: Hasil Dan Pembahasanunclassified